PENGARUH GAYA KEPEMIMPINAN TERHADAP PENGAMBILAN KEPUTUSAN - Daffa Ramadhan, Muhammad; Lumban Siantar, Petrus Bekam; Rosalina, Sinta (Journal for Management Student (JFMS), 2022)
This research examines the Influence of Leadership Style in Decision Making. The method carried out is the "table" research method through a literature study approach, as well as making conclusions and suggestions. The data contained in this article is obtained from various written sources regarding leadership and decision making, such as books, scientific journals and relevant and reliable scientific articles.   The results of this study concluded that the leadership style of a leader can influence what decisions are made. Each type of leadership will take decisions in different ways, as well as different decision outcomes as well.   Keywords: Leadership Style and Decision Making